Environment, Social, and Governance (ESG) Mapping of Islamic Entrepreneur Boarding School (IEBS) Global Cahaya Nubuwwah Insani (GCNI) Foundation - Idrianita Anis; Juniati Gunawan; Henik Heru Astuti; AA Hubu; Andi Oktavianus Lawrens; Andre Mandala Putra; Ayuni Fitria; Nicholas Kim Jiro; Adzana Widhiatama Suparjo (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2026)
This community engagement program (PkM) systematically mapped and strengthened the Environmental, Social, and Governance (ESG) readiness of the Islamic Entrepreneur Boarding School (IEBS) at the Global Cahaya Nubuwwah Insani (GCNI) Foundation, Purwakarta. The program integrated pre- and post-intervention ESG literacy assessment, institutional ESG scoring, participatory sustainability mapping, and maturity classification to produce a structured diagnostic framework tailored to pesantren-based micro, small, and medium-sized enterprises (MSMEs). A total of 40 participants completed baseline and post-intervention questionnaires, indicating a statistically significant improvement in ESG literacy (mean difference = 1.625; t = 13.275), which was categorized as a high-impact outcome. Institutional ESG assessment using 40 indicators across Environmental, Social, and Governance dimensions yielded an overall ESG Index of 61.67%, placing the institution in the Developing (Programmatic) stage. The Social dimension demonstrated strong institutional embedding, whereas Environmental practices were operational but only partially measured, and Governance systems required further formalization. A dual-scoring mechanism that combined self-assessment with external validation enhanced reliability and reduced evaluation bias. The findings indicate that IEBS GCNI is transitioning from value-driven sustainability to more structured ESG governance. This study contributes a replicable ESG mapping framework that bridges green economy regulation with Islamic entrepreneur boarding school governance and supports sustainable MSME ecosystem development.